Adherence, persistence, and inpatient utilization among adult schizophrenia patients using once-monthly versus twice-monthly long-acting atypical antipsychotics. (1st February 2018) - Pilon, Dominic; Alcusky, Matthew; Xiao, Yongling; Thompson-Leduc, Philippe; Lafeuille, Marie-Hélène; Lefebvre, Patrick; Benson, Carmela
Abstract: Aims: This study compared healthcare resource utilization (HRU), healthcare costs, adherence, and persistence among adult patients with schizophrenia using once-monthly (OM) vs twice-monthly (TM) atypical long-acting injectable (LAI) antipsychotic (AP) therapy. Materials and methods: A longitudinal retrospective cohort study was conducted using Medicaid claims data from six states. Patients initiated on aripiprazole or paliperidone palmitate were assigned to the OM cohort; risperidone-treated patients were assigned to the TM cohort. HRU and healthcare costs were assessed during the first 12 months following stabilization on the medication. Adherence was measured using the proportion of days covered (PDC) during the first year of follow-up. Persistence to the index medication was measured during the first 2 years following the index date. Comparison between the cohorts was achieved using multivariable generalized linear models, adjusting for demographic and clinical characteristics. Results: Patients in the OM LAI cohort had lower inpatient HRU and medical costs when compared with patients in the TM cohort. Higher medical costs in the TM LAI cohort offset the higher pharmacy costs in the OM LAI cohort. Mean PDC during the first 12 months of follow-up was higher in the OM cohort than in the TM cohort (0.56 vs 0.50, p  < .01). Median persistence was longer in the OM cohort than in the TM cohort (7.5 months vs 5.5 months), as was the hazard of discontinuing the index medication (hazard ratio = 0.83, p  = .01). Kaplan-Meier rates of persistence at 1 year were higher for OM patients than for TM patients (37.6% vs 29.6%, p  < .01). Limitations: This was a Medicaid sample with few aripiprazole LAI patients (5.4% of OM cohort). Medication use was inferred from pharmacy claims. Conclusions: Among Medicaid patients in these six states, OM AP treatment was associated with lower HRU, better adherence and persistence, and similar total costs compared to patients on TM treatment.